Emissão de metano entérico e parâmetros comportamentais de bovinos tropicais em sistema silvipastoril - Frota, Marcílio Nilton Lopes da (2017)
Objective of this work was to evaluate the enteric methane emission, animal performance, forage availability and nutritional value of Mombasa grass intercropped with Babaçu (silvipastoril) compared to a monoculture pasture in the Cocais region. Evaluations took place in the dry season (May to August 2015) and in the rainy season (January to April 2016). Experimental design for the pasture evaluations was completely randomized. The treatments corresponded to the pasture type. For animal evaluations, the independent variables were: live weight, daily weight gain (DWG kg), dry matter intake (DMI kg), day methane emission, methane kilo year, methane emission in gram per kilogram of live weight, methane emission in gram per kilogram of DWG, methane emission in gram per kilogram of DMI, gross energy loss in the form of methane, including fixed animal effects, collection period and treatment. Six steers were used in each system with initial weights of 185 (± 26) kg. Each area was divided into 7 pickets of 4,200 m². For the determination of the forage mass, the zero cut technique of each picket was used. Total forage dry matter mass, dry mass of green forage (DMGF), dry mass of leaf blades, dry mass of stalks, dry forage of dead forage, relation forage forage / dead forage and leaf / stem ratio were determined. For analysis of the nutritive value, simulated grazing was performed and the dry matter (DM), crude protein (CP), fiber, ethereal stratum, total carbohydrate, NDT , calcium and phosphorus were determined. The in vitro digestibility of MS was determined using Ankom® automatic apparatus. Determination of the amount of CP (kg ha-1) was obtained by multiplying the mean CP content of the forage by the DMGF. The dry matter consumption through LIPE®, the emission of enteric methane by sulfur hexafluoride tracer gas and animal performance were simultaneously evaluated. The forage availability was not influenced by the type of pasture in the same period of the year, showing no differences between the treatments. Regarding the amount of CP, there were differences only in this period, the silvopastoral system presented twice the CP in relation to the monoculture. Emissions per animal in the systems were similar in the same period around 45 kg / year (dry season) and 70 kg / year (rainy season). In the dry period the emission intensity (kg of CH4 per DWG) was lower, there were differences in relation to the loss of gross energy by CH4. The silvipastoral system presented less loss. In the rainy season, there was a higher intake of dry matter, with no differences between treatments, the DWG was around 1 kg / day. In this way, the silvopastoral system resembles the monoculture pasture system that has undergone a deforestation stage. The fact of clearing the whole area did not offer productive advantages nor in the emission of methane. The silvopastoral system is a more sustainable mode of production under the conditions studied.